STEAM-Based Learning Media: Assisting in Developing Children’s Skills - Rachma Hasibuan; Ruqoyyah Fitri; Utari Dewi (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
STEAM is a learning approach combining science, technology, engineering, arts/creativity, and mathematics. STEAM is not only a part of group studies, but also holistically integrates multiple approaches to solve problem. This research is a type of developmental research that aims to create a STEAM-based learning media for early childhood education through the ADDIE model. The data were collected from through one-group pretest-posttest design and analyzed according to the ADDIE developmental research technique. Participants of this research were young children aged 4-6 years who attended preschool and ECE teachers. The result shows that the developed media are proved to be valid in term of material and media feasibility. Moreover, it shows its practicality and effectiveness which comply with the standard use for early childhood education learning media; thus, it indicates that the developed media can be implemented as learning media for early childhood edu